Importin-mediated retrograde transport of CREB2 from distal processes to the nucleus in neurons - Lai, Kwok-On (National Academy of Sciences, 2008)
Signals received at distal synapses of neurons must be conveyed to the nucleus to initiate the changes in transcription that underlie long-lasting synaptic plasticity. The presence of importin nuclear transporters and of select transcription factors at synapses raises the possibility that importins directly transport transcription factors from synapse to nucleus to modulate gene expression. Here, we show that cyclic AMP response element binding protein 2 (CREB2)/activating transcription factor 4 (ATF4), a transcriptional repressor that modulates long-term synaptic plasticity and memory, localizes to distal dendrites of rodent hippocampal neurons and neurites of Aplysia sensory neurons (SNs) and binds to specific importin α isoforms. Binding of CREB2 to importin α is required for its transport from distal dendrites to the soma and for its translocation into the nucleus. CREB2 accumulates in the nucleus during long-term depression (LTD) but not long-term potentiation of rodent hippocampal synapses, and during LTD but not long-term facilitation (LTF) of Aplysia sensory-motor synapses. Time-lapse microscopy of CREB2 tagged with a photoconvertible fluorescent protein further reveals retrograde transport of CREB2 from distal neurites to the nucleus of Aplysia SN during phenylalanine-methionine-arginine-phenylalanine-amide (FMRFamide)-induced LTD. Together, our findings indicate that CREB2 is a novel cargo of importin α that translocates from distal synaptic sites to the nucleus after stimuli that induce LTD of neuronal synapses.